Pyrrolic nitrogen dominated the carbon dot mimic oxidase activity. (July 2021) - Wang, Huibo; Zhang, Mengling; Wei, Kaiqiang; Zhao, Yajie; Nie, Haodong; Ma, Yurong; Zhou, Yunjie; Huang, Hui; Liu, Yang; Shao, Mingwang; Kang, Zhenhui
Abstract: Carbon dots (CDs) with enzyme-like activities play crucial roles in nanobiotechnology. However, it is difficult to establish a relationship between their structure and biocatalytic properties. In this work, a series of nitrogen-doped carbon dots (TA-NCDs) were synthesized by a hydrothermal method. Their oxidase-like activity could be triggered by visible light irradiation (420 nm≤λ ≤ 700 nm). As a nanozyme, TA-NCDs show the value of maximum reaction rates (Vmax ) is 121.95 × 10 −8  M/s and the Michaelis–Menten constants (Km ) is 0.61 mM. In situ transient photovoltage (TPV) tests prove that the pyrrolic nitrogen in TA-NCDs is the catalytic active sites and substrate binding sites. Under visible light irradiation, TA-NCDs, with oxidase-like activity, increased the cellular ROS level significantly, leading to their visible light induced bioactivity to kill nearly 60% of HeLa cells. Graphical abstract: Pyrrolic nitrogen dominated the mimic oxidase activity of CDs. Image 1 Highlights: TA-NCDs exhibit oxidase-like activity under visible light irradiation. The maximum velocity of TA-NCDs is 121.95 × 10 −8  M/s, implying TA-NCDs show higher catalytic activity than natural enzyme. In situ TPV test was used to explore the active sites of TA-NCDs. The application of TA-NCDs in physiological environments was confirmed.